The limitations and opportunities to implement environmental management system in Malaysia - Megat Abdullah, Aminatuzuhariah (Fakulti Alam Bina, UTM, 2006)
This paper highlights the extent of the Environmental Management System (EMS) implementation in building and construction industry in Malaysia. It has been found from the literature review and the research done, that the implementation of the EMS approaches in building professional organisations is still at the infancy stage. This paper also presents some approaches that can be taken to address the present obstacles that hinder a wider implementation of environmental sustainable development